2007
DOI: 10.1186/1742-4690-4-25
|View full text |Cite
|
Sign up to set email alerts
|

Sequential emergence and clinical implications of viral mutants with K70E and K65R mutation in reverse transcriptase during prolonged tenofovir monotherapy in rhesus macaques with chronic RT-SHIV infection

Abstract: Background: We reported previously on the emergence and clinical implications of simian immunodeficiency virus (SIVmac251) mutants with a K65R mutation in reverse transcriptase (RT), and the role of CD8+ cell-mediated immune responses in suppressing viremia during tenofovir therapy. Because of significant sequence differences between SIV and HIV-1 RT that affect drug susceptibilities and mutational patterns, it is unclear to what extent findings with SIV can be extrapolated to HIV-1 RT. Accordingly, to model H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 87 publications
3
62
0
Order By: Relevance
“…Previous studies have shown that SIV and HIV share similar resistance patterns against different classes of ARVs (10,36,37). Additionally, tissue culture studies by our group demonstrated that SIV substitutions confer resistance against INSTIs in a similar fashion to HIV (12).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Previous studies have shown that SIV and HIV share similar resistance patterns against different classes of ARVs (10,36,37). Additionally, tissue culture studies by our group demonstrated that SIV substitutions confer resistance against INSTIs in a similar fashion to HIV (12).…”
Section: Discussionmentioning
confidence: 65%
“…A long-acting form of a new INSTI, cabotegravir (also known as S/GSK-1265744), which is a DTG analogue, was shown to protect macaques against repeated vaginal and rectal challenges using SHIV (7,8). Prolonged TFV monotherapy of macaques infected with SIV or SHIV resulted in the emergence of viral mutants with the K65R substitution in RT, the same mutation that is associated with TFV treatment failure (9,10). In another study, macaques treated during preexposure prophylaxis with emtricitabine (FTC) or Truvada (TFV and FTC) and later infected by SIV sometimes developed the M184V substitution in RT, which is associated with resistance to FTC in HIV (11).…”
mentioning
confidence: 99%
“…To further substantiate that conclusion, and to determine if the atypical course of infection in the 3 animals with transient viremia was due to strong cell-mediated antiviral immune responses, an in vivo CD8 ϩ cell depletion experiment was performed. At 58 weeks after SIV inoculation, the three animals were administered an anti-CD8 antibody that in previous studies induced a transient increase in viremia in SIV-infected animals (31,55,56). Following a single infusion of anti-CD8 antibody M-T807R1, the CD3 ϩ CD8 ϩ T cell and CD3 Ϫ CD8 ϩ NK cell counts in peripheral blood were undetectable or very low (Յ5 per l) for 3, 8, and 9 weeks in animals 32787, 30285, and 32214, respectively (Fig.…”
Section: Cd4mentioning
confidence: 99%
“…The primary resistance mutation to FTC has been studied for its effects on in vivo viral virulence and fitness (Van Rompay et al, 2002a). Similarly, mutations conferring resistance to tenofovir were studied in SIV for their emergence and suppression in vivo during tenofovir monotherapy (Van Rompay et al, 2007). Resistant viruses were identified in macaques with breakthrough infections after intermittent tenofovir/FTC pre-exposure prophylaxis with intrarectal challenge (Garcia-Lerma et al, 2008).…”
Section: Drug Resistancementioning
confidence: 99%